The Monument to Independence as an event: No nos cuidan, nos violan, they do not protect us, they rape us - R. Guy Emerson (European Review of Latin American and Caribbean Studies, 2022)
On August 16, 2019, protesters arrived at the Monument to Independence in Mexico City. In response to three separate allegations of rape by police in less than a month, demonstrators scrawled 565 pieces of graffiti to transform a historical site of national commemoration into a symbol of state violence against women. 'México feminicida' (Mexico is femicide) covered the central plaque that previously read: ‘[from] the Nation to the Heroes of Independence’. The paper explores this transformation. Informed by Alfred North Whitehead, it argues that the Monument to Independence is an event. It is neither a timeless tribute to the nation, nor is it merely situated along the manicured 'Paseo de la Reforma'. Rather, the Monument is continually reproduced in how graffiti connects it up with multiple histories of gender-based violence, in how it is given to meaning through the assembly of female/feminine bodies. From one of the most sedimented artifices of national remembrance, the site is transformed into a monument to patriarchal domination; a transformation that persists despite subsequent restoration work. Resumen: El monumento a la independencia como acontecimiento: No nos cuidan, nos violan El 16 de agosto de 2019, los manifestantes llegaron al Monumento a la Independencia en la Ciudad de México. En respuesta a tres denuncias distintas de violación por parte de la policía en menos de un mes, los manifestantes garabatearon 565 grafitis para transformar un sitio histórico de conmemoración nacional en un símbolo de la violencia de Estado contra las mujeres. 'México feminicida' cubrió la placa central que antes decía: “De la Nación a los Héroes de la Independencia”. El documento explora esta transformación. Basándose en Alfred North Whitehead, sostiene que el Monumento a la Independencia es un acontecimiento. No se trata de un tributo intemporal a la nación, ni de un mero emplazamiento a lo largo del Paseo de la Reforma. Más bien, el Monumento se reproduce continuamente en cómo el grafiti lo conecta con múltiples historias de violencia de género y le da significado a través del ensamblaje de cuerpos femeninos. De uno de los artificios más sedimentados de la memoria nacional, el sitio se transforma en un monumento a la dominación patriarcal; una transformación que persiste a pesar de los trabajos de restauración posteriores.